Stress-strain state of space grid structure - Sribniak, Nataliia; Tsyhanenko, Liudmyla; Tsyhanenko, Hennadii; Halushka, Serhii (Academic journal Industrial Machine Building Civil Engineering, 2020)
One of the factors influencing the stress-strain state of the structure is the placement method of the columns and their step. The problem formulated in the article is to determine the design solution of the space grid structure with the least weight. The paper examines how the columns location, the number of support points, and the supports step affect the force values in the space grid structure rods and the supports (columns). The first variant of the model adopted a space grid structure supported in the corners of four columns. The second variant of the model adopted a space grid structure supported on two sides – six columns on each side. In the third variant, the structure is supported by 20 columns along the perimeter. It has been determined that the third method of supporting location is the most efficient.
Keywords: material capacity; optimization; space grid structure; stress-strain state regulation; tension regulator